Hubungan Status Gizi dan Tingkat Pengetahuan Gizi Seimbang terhadap Kejadian Hipertensi Lansia Di Kecamatan Bulu Kabupaten Sukoharjo - Irma Handayani; Aryanti Setyaningsih; Arwin Muhlishoh (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2024)
Factors that can increase the incidence of hypertension are the state of a person's body associated with a state of excess nutrition that leads to obesity and lack of nutritional knowledge related to the management of hypertension.This study aims to determine the relationship between nutritional status and level of knowledge about balanced nutrition on the incidence of hypertension in the elderly in bulu district, sukoharjo regency. Observational research with a cross sectional research design which was conducted in June-July 2022.There were 101 respondents who participated in this study by interviewing respondents using a balanced nutrition knowledge questionnaire and measuring Body Mass Index (BMI) and blood pressure was measured using a digital sphygmomanometer. Data analysis used the Spearman correlation test with a significance level of 95%. There is a relationship between the incidence of hypertension in the elderly in bulu district with nutritional status (p = 0.044; r= 0,710) and the level of knowledge about balanced nutrition (p = 0.027; r= 0,118). There is a relationship between nutritional status and the incidence of hypertension and there is a relationship between the level of knowledge about balanced nutrition and the incidence of hypertension, so it is recommended that the elderly can maintain normal nutritional status and can apply the knowledge received in daily life in order to maintain blood pressure in normal conditions.